Respuesta :
1. First, you must change [tex] f(x) [/tex] for [tex] y [/tex]. Then, you need to switch [tex] x [/tex] and[tex] y [/tex] and solve for [tex] y [/tex], as following:
[tex] y=-\frac{1}{2}\sqrt{x+1} \\ x=\frac{1}{2}\sqrt{y+1}\\ x^{2} =(\frac{1}{2}\sqrt{y+1})^{2}\\ x^{2} =\frac{1}{4}(y+1)\\ y=4x^{2} -1 [/tex]
2. Therefore, you have:
[tex] f^{-1}(x)=4x^{2} -1 [/tex]
The answer is: [tex] f^{-1}(x)=4x^{2} -1 [/tex]
Answer
f⁻¹(x) = 4x² - 1
f⁻¹(x) ≥ 35
Explanation
The function to find the inverse for is;
f(x) = -1/2 × √(x-1), x ≥ -3
First equat the function to y the make x the subject of the formula.
y = -1/2 × √(x-1)
Square both sides of the equation
y² = 1/4 ×(x+1)
Multiplying both sides by 4
4y² = x+1
Subtracting 1 from both sides.
x = 4y² - 1
Now interchange x and y.
y = 4x² - 1
The inverse of f(x) = 1/2 × √(x-1) is;
f⁻¹(x) = 4x² - 1 , x ≥ -3
f⁻¹(x) = 4×(-3)² -1
= (4×9) - 1
=36 - 1
=35
Answer,
f⁻¹(x) ≥ 35